Digital modeling and its technical variables in contemporary interior design (Al-Academy, 2023)
The current research sheds light on an important aspect of the great and rapid development in the field of science and technology and modern manufacturing methods as a result of the scientific revolution resulting from the accelerated cognitive development, which prompted designers in general and interior design in particular to exploit and invest in digital technology and the development of digital control in the process of designing the industrial product for the purpose of creativity and innovation through these digital programs Digital models achieve the requirements and desires of the interior designer according to the creative skill using modern software with high efficiency And extreme accuracy that is consistent with the requirements of the user, interior designer and beneficiary companies.Therefore, the research problem can be identified by the following question: What is the nature of the variables in the modeling patterns in the stages of contemporary interior space design through the use of virtual reality techniques?, While the aim of this study was: to reveal the importance of digital models in the real internal space through virtual reality outputs, the current research included three topics The first topic: variables and their relationships Interior space design, The second topic: modeling in interior design between reality and simulation, and the third topic: digital models in interior design, and the research reached a set of conclusions, the most important of which are:1. Digital models allow the designer, beneficiary organizations and people to explore the interior space before it is designed.2. Designers use Digital Prototyping to design, optimize, validate, and visualize their spaces digitally throughout the design stages.3. Innovative digital models can be created through creative designs, achieving multiple design objectives (best performance, high efficiency, space effectiveness, appropriate cost)Keywords: Digital, modeling, interior designSearch problem:Testing the outputs of the design process and verifying the extent to which they achieve the goals and address failures or development on the design itself is one of the first priorities of companies and design centers and is widely used in digital models since the start of the process and achieves its goals by increasing revenues, reducing cost, speed of delivery, and achieving quality conditions, and companies that use digital models achieve 86% superiority of their counterparts that use traditional prototypes, as well as a precedence rate from the design stages to the start of production in record time. It costs relatively less, which gives it priority in competition as well as speed of implementation (Aberdeen Group, October 2006,p. i)The rapid development in the cognitive systems pushed designers in general and the interior designer in particular to exploit and invest in digital technology and the development of digital control in the process of designing the industrial product for the purpose of creativity and innovation through these digital programs Digital models achieve the requirements and desires of the interior designer according to the creative skill using modern software with high efficiency and extreme accuracy consistent with the requirements of the user, interior designer and beneficiary companies.Therefore, the research problem can be identified by the following question: What are the digital modeling techniques in the design of the virtual indoor space and what are their variables?The importance of research:The importance of the current research lies in:1- Addressing a topic that enriches the knowledge of modeling patterns variables in the inner space.2- The results of the study serve the relevant institutions of designers and researchers